2016
DOI: 10.1039/c6tc01540a
|View full text |Cite
|
Sign up to set email alerts
|

A facile hybrid approach to high-performance broadband antireflective thin films with humidity resistance as well as mechanical robustness

Abstract: Broadband high transmittance, humidity resistance and mechanical robustness are three important aspects that dictate the practical applications of antireflective thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
1
18
1
Order By: Relevance
“…This approach provides a viable alternative for the testing of environmental durability of coatings, compared to the standard tests that involve exposing the sample to constant RH values for extended periods of time followed by measurement of the material properties ex situ. 19,46 In earlier works on silica-based networks, repeated cycles of water adsorption and desorption demonstrated an impact on the mechanical integrity of the porous skeleton as well as hydrophobicity via capillary stresses and irreversible adsorption of water molecules within the pores. 47−49 In the present study, the ARC 1:1f sample maintained both its hydrophobicity and AR capabilities after 50 EP cycles.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…This approach provides a viable alternative for the testing of environmental durability of coatings, compared to the standard tests that involve exposing the sample to constant RH values for extended periods of time followed by measurement of the material properties ex situ. 19,46 In earlier works on silica-based networks, repeated cycles of water adsorption and desorption demonstrated an impact on the mechanical integrity of the porous skeleton as well as hydrophobicity via capillary stresses and irreversible adsorption of water molecules within the pores. 47−49 In the present study, the ARC 1:1f sample maintained both its hydrophobicity and AR capabilities after 50 EP cycles.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…Meanwhile, as shown in Fig. 4, the moth-eye thin film also shows a more broadband AR property in contrast to the smooth nanoporous AR film derived only from a proper porosity 29 in the wavelength range of 750–1500 nm, indicating the nipples array of the film with a moth-eye effect also contributes to the optical properties besides the nanopores. In addition, the transmittances of the moth-eye thin film and glass substrate over incidence angles ranging from 0 to 60° were measured.…”
Section: Resultsmentioning
confidence: 93%
“…1 mm thick) at room temperature with a relative humidity of 15–20%. Finally, the as-prepared film was solidified at 60 °C, ultrasonically cleaned by water and calcined at 500 °C for 1 h. The smooth thin films were prepared by dip-coating the methyl-silica hybrid sol 29 . The control samples in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[23,24] However, the inorganic fillers may deteriorate the optical transparency of the polymers by light scattering. [25][26][27][28][29] Thus, it is extremely challenging to achieve the enhancement of thermomechanical property without losing optical transparency. Okahisa et al reported optically transparent nanocomposites with a bacterial cellulose filler, [30] in which bacterial cellulose (50 nm wide) nanofibers appear virtually free from light scattering.…”
Section: Introductionmentioning
confidence: 99%